The Effect Of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on Financial Performance - Pertiwi, I Dewa Ayu Eka; Dewi, Dewa Ayu Puspita; Kawisnawa, Putu Gede Wisnu Permana (GOVERNORS, 2023)
This study aims to empirically examine the effect of Corporate Social Responsibility and Good Corporate Governance on the financial performance of banking companies listed on the Indonesia Stock Exchange in 2017-2020. The research method used in this study is a quantitative method. The population in this study were all banking companies listed on the Indonesia Stock Exchange in 2017-2020, where the sample used was purposive sampling criteria and obtained as many as 10 banking companies. The data analysis technique used in this study is multiple linear regression analysis, F test, and t test. Based on the research results, it can be seen that Corporate Social Responsibility has a negative and insignificant effect on the financial performance of banking companies. The reason is because Corporate Social Responsibility activities in Indonesia are still based on volunteerism, so that many companies still consider Corporate Social Responsibility activities as a burden that can reduce company profits and have no effect on financial performance. In addition, the results of this study also found that Good Corporate Governance (which is proxied by the proportion of the number of commissioners and directors) has a positive and significant effect on the financial performance of banking companies. The reason is that the more the number of boards of commissioners and the board of directors in a company can help create good governance within the company, so that the creation of good governance within a company can help improve financial performance.